Navigating the Talent Shift How to Build On-Demand Teams that Drive Innovation, Control Costs, and Get Results - Hufford, Lisa (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
By 2020, 40 percent of the workforce won't want to be your employee. That means managers and executives have to forget the old recruit-and-search for-months methods to acquire talent and revise their perception that "talent" is only full-time employees. The good news is that this talent allows you to achieve the biggest impact on your projects in the fastest time possible.  In Navigating the Talent Shift, author Lisa Hufford  introduces you to SPEED: a fast, and flexible talent strategy that shows companies how to access the 65 million people that make up the on-demand, specialized talent pool. This strategy shows you how to: • Stop spending months searching for talent • Have a team of on-demand talent at your fingertips • Exponentially expand your talent pool  • Test ideas and change direction fast to stay competitive and drive innovation • Reduce severance and layoffs • Bring a fresh perspective with strategic doers on your team • Do more with less Navigating the Talent Shift will show you and your team how to tap into an on-demand workforce while providing you with the talent you need to be nimble and successful.  .